Heterologous expression of mlrA gene originated from Novosphingobium sp. THN1 to degrade microcystin-RR and identify the first step involved in degradation pathway. (October 2017) - Wang, Ruiping; Li, Jieming; Jiang, Yongguang; Lu, Zhijiang; Li, Renhui; Li, Ji
Abstract: Information on the catalytic role of mlrA gene-encoded enzyme (MlrA) in microcystin-RR (MC-RR) biodegradation was limited. This study succeeded in expressing mlrA homolog of Novosphingobium sp. THN1 in heterologous host for the first time, by constructing a recombinant bacterium. Mass spectrometric analysis showed that the recombinant MlrA hydrolyzed MC-RR into linear intermediate product by cleaving the peptide bond between Adda and arginine residue, greatly detoxifying MC-RR. This finding clearly manifested that the MlrA homolog of THN1 strain possesses its original catalytic function, and ring-opening constituted the first step in MC-RR biodegradation pathway of THN1 strain. Moreover, MC-RR degradation by intact recombinant cells and cell-free crude enzyme (CE) from recombinant was compared. Results exhibited that intact recombinant was able to degrade 20 μg mL −1 MC-RR more quickly than CE, with the maximum rate of 9.22 μg mL −1 h −1 in the first 8 h. Thus, this study provided new insights on the catalytic activity and roles of MlrA originated from THN1 strain in MC-RR biodegradation process, which lay a foundation for efficiently removing and detoxifying MC-RR, and exploring downstream steps in MC-RR biodegradation pathway of THN1 strain. Highlights: This study succeeded in heterologous expression of mlrA from Novosphingobium sp. THN1. Expressed MlrA caused linearization of microcystin-RR by cleaving Adda-arginine bond. Ring-opening constituted the first step in microcystin-RR degradation pathway of THN1. Intact recombinant had higher microcystin-RR degradability than crude enzyme extract. This study shed the activity and roles of MlrA in microcystin-RR degradation by THN1.